ENGENDERING THE REFUGEE CRISIS IN EUROPE (Annual of the Faculty of Philosophy in Skopje, 2019)
Since the beginning of 2015, Europe has been facing a refugee crisis wherethousands of people have risked their lives to reach European soil. European politiciansand media labelled this crisis as a new issue for the EU, not because the crisiswas an entirely new phenomenon, but due to the staggering increase in the numberof refugees from conflict areas, most notably Syria, Afghanistan, Eritrea, and Somalia.In 2015 alone, over one million refugees sought asylum in Western Europe. Themajority of these had travelled through Turkey, Greece, and the Western Balkans toreach their final destination. The perils they faced during that route have been recordedin many of the reports by the International organization for migration (IOM),the UN Security Council, and many other organizations and departments involvedin the crisis. In spite of all this, very little attention has been paid to the gender dimensionof this refugee crisis, the problems women have been facing, the treatmentthey have been given, and the steps taken to help protect their human rights aboveall, but also their rights to services directly meeting their specific needs.
Keywords: REFUGEE CRISIS; GENDER; VIOLENCE; SEXUAL VIOLENCE; EU; POLICIES